PWE-245 Oral neostigmine treatment in recurrent resistant intestinal pseudo-obstruction. (22nd June 2015) - Mirza, NM; Akram, A; Konrad, K
Abstract : Introduction: Chronic intestinal pseudo-obstruction is a syndrome of disordered intestinal motility. It is generally considered to be more prevalent in elderly patients so incidence is expected to rise in developed countries with ageing population. Chronic pseudo-obstruction can be difficult to treat and has significant morbidity. Neostigmine has been reported to effectively relieve acute colonic pseudo-obstruction. Reported recurrence after initial use of neostigmine is up to 30%. Neostigmine enhances excitatory parasympathetic activity by competing with acetylcholine for attachment to acetylcholinesterase at sites of cholinergic transmission and enhancing cholinergic action. We studied use of oral neostigmine treatment for six months in patients with recurrent resistant pseudo-obstruction when other treatments failed and surgery was not considered a safe option due to co-morbidities. Method: Three patients with clinical and radiological evidence of pseudo-obstruction were treated conservatively. All reversible causes were corrected and two patients had multiple flatus tube inserted for colonic decompression with recurrence of pseudo-obstruction. After deemed, unsafe for surgical intervention secondary to co-morbidities, patients were treated with 2.5 mg intramuscular neostigmine and then maintenance dose of oral Neostigmine 30 mg twice daily was initiated. Regular ECG was carried out pre and post treatment to look for cardiac arrhythmias. Patients were monitored for side effects and recurrence of symptoms. Results: Clinical resolution of large bowel dilatation occurred in all three patients within twenty four hours after initiating treatment with intramuscular neostigmine. Maintenance oral Neostigmine 30mg twice daily was continued for six months with no further recurrence of pseudo-obstruction. No side effects or complications were noted. Conclusion: We have shown that oral Neostigmine is safe and effective treatment option in selective group of patients with recurrent resistant pseudo-obstruction when other conservative treatment options are ineffective. Disclosure of interest: None Declared.